Monitor the Growth and Oxidation of Cu-nanoparticles in PEG after Sputtering. (24th January 2019) - Chau, Yuen-ting Rachel; Deng, Lianlian; Nguyen, Mai Thanh; Yonezawa, Tetsu
ABSTRACT: Metallic Copper nanoparticles (Cu NPs) were obtained via sputtering of Cu target onto liquid polymer, i.e., poly(ethylene glycol), PEG, under vacuum condition. The Cu NPs growth significantly right after the sputtering deposition from 3.1 nm to 4.1 nm in 4 hours as monitored by TEM. There was negligible growth of NPs for longer time and completely PEG acts as the coating material of Cu NPs so no agglomeration was observed for 1 week. The challenge of characterization of Cu NPs was also discussed.